Peran Gerakan Nasional Orang Tua Membacakan Buku di PAUD Nurul Amal Bandung - Lina Kamila Rahmasari; Lutfi Khoerunnisa (Fakultas Ilmu Komunikasi Universitas Islam Nusantara, 2022)
The role of the family is very important to improve children's literacy skills, because the family is the smallest unit in society and is the first learning environment for children. Emotional closeness between children and parents can be used to instill good habits from childhood. The National Movement for Parents Reading Books to Children (GERNAS BAKU) is a movement to support the role of families in fostering children's interest in reading through habituation at home, in PAUD or in the community. PAUD Nurul Amal is one of the PAUD institutions in the city of Bandung that seeks to promote the GERNAS BAKU program so that the Beginning Reading Ability of early childhood children is increased. Activities carried out at the Nurul Amal PAUD institution for GERNAS BAKU include (1) holding a socialization on what GERNAS BAKU is. (2) Activities for parents to read books at school. (3) Further review is carried out through Gernas Baku Activities at home. Gernas Baku was successfully carried out at the PAUD Nurul Amal institution, it is proven that the early reading ability of children is increasing. This activity aims to teach parents how to get used to reading storybooks from an early age, strengthen social-emotional relationships between children and parents, and improve early reading skills in children aged 5-6 years.Keywords: Gernas Baku, interest in reading, early childhoodABSTRAKPeran keluarga sangat penting untuk meningkatkan kemampuan literasi anak, karena keluarga merupakan unit terkecil dalam masyarakat dan merupakan lingkungan pembelajaran yang pertama untuk anak. Kedekatan emosional antar anak dan orang tua dapat dimanfaatkan untuk menanamkan kebiasaan baik sejak kecil. Gerakan Nasional Orang Tua Membacakan Buku Kepada Anak (GERNAS BAKU) merupakan gerakan untuk mendukung peran keluarga untuk menumbuhkan minat baca anak melalui pembiasaan di rumah, di PAUD ataupun di masyarakat. PAUD Nurul Amal adalah salah satu lembaga PAUD yang berada di kota Bandung yang berupaya menggalakkan program GERNAS BAKU agar Kemampuan Membaca Permulaan anak-anak usia dini meningkat. Kegiatan yang dilakukan di lembaga PAUD Nurul Amal ini untuk GERNAS BAKU di antaranya (1) mengadakan sosialisasi apa itu GERNAS BAKU. (2) Kegiatan Orang Tua membacakan buku di Sekolah. (3) Dilaksanakan tinjauan lebih lanjut melalui Kegiatan Gernas Baku di rumah. Gernas Baku berhasil dilakukan di lembaga PAUD Nurul Amal, ini terbukti bahwa kemampuan membaca permulaan anak menjadi meningkat. Kegiatan ini bertujan untuk mengajarkan ke orang tua cara membiasakan membacakan buku cerita sejak usia dini, mempererat hubungan sosial emosional antara anak dan orang tua, serta meningkatkan kemampuan membaca permulaan pada anak usia 5-6 tahun.